Bariatric surgery patients in AUD treatment in Norway—an exploratory cross-sectional study. - Bramness, Jørgen G; Lien, Lars; Moe, Jenny S; Toft, Helge; Pandey, Susmita; Lid, Torgeir G; Strømmen, Magnus; Andersen, John R; Bolstad, Ingeborg (Alcohol & Alcoholism, 2024)
Aims Patients who have undergone some forms of bariatric surgery have increased risk of developing alcohol use disorder (AUD). In the present observational study, we compared patients with AUD who themselves reported to having undergone bariatric surgery with other patients in treatment for AUD. Materials One-hundred-and-six consecutively enrolled patients in residential treatment for AUD were asked if they had undergone bariatric surgery. Sociodemographics, mental health-related, and alcohol use-related parameters were compared between those who had and those who had not undergone bariatric surgery. Results Of the 106 patients with AUD, seven (6.6%; 95% confidence interval, 2.7%–13.1%) had undergone bariatric surgery. Six of seven patients had undergone such surgery were women (P  < .001). The patients with AUD who had undergone bariatric surgery were similar to other patients with AUD on most other parameters, the exception being a larger number of alcohol units ingested to feel an effect of alcohol (adjusted odds ratio 7.1; 95% confidence interval 2.0–12.2; P  = .007). Conclusion The high number of patients with AUD that reported having undergone bariatric surgery emphasizes the risks following such a procedure. The overrepresentation of women may reflect than more women undergo such procedures. The unexpected finding that patients with AUD having undergone bariatric surgery seemed to need more alcohol to feel intoxicated warrants further research.